Long noncoding RNA ENST00000508435 promotes migration of breast cancer via FXR 1. Issue 1 (1st January 2021) - Li, Luying; Jin, Youping; Wang, Xue; Wang, Li; Sun, Yangbai; Luo, Yihong; Ni, Xiaojian; Lu, Qi; Wei, Wenbo; Zhi, Xiuling; Yu, Jerry; Zhu, Wei; et al.
ABSTRACT: LncRNA plays a critical role in tumor progression. However, the role it executes in breast cancer is still unclear. Here, we report a newly discovered lncRNA, ENST00000508435, which could be remarkably up-regulated in breast cancer cells and tissues. We found that the expression of ENST00000508435 was positively correlated with tumor size, lymph node metastasis and HER2. More interesting, overexpression of ENST00000508435 significantly increased cell migration, while specific knockdown led to the opposite. RNA pull-down and RNA immunoprecipitation assays demonstrated that ENST00000508435 could directly bind to FXR1 to promote tumor metastasis. ENST00000508435 and FXR1 were positively correlated. FXR1 was also significantly up-regulated in breast tumors. Taken together, we propose that ENST00000508435 regulates FXR1 to promote breast cancer metastasis.